How Strategic Flexibility Affects Digital Transformation: Empirical Study On Modern Coffee Shops in Indonesia - Khristianto, Wheny; Trihartono, Agus; Wahyudi, Edy (Indonesian Journal of Business and Entrepreneurship, 2023)
Modern coffee shop industry players face changes in their environment that require them to adapt their actions and strategies very quickly. In this highly competitive environment, resources have become essential for companies that influence strategic flexibility. For companies, strategic flexibility is obtained when an organization develops or obtains a series of actions that enable it to outperform its competitors. In a dynamic and rapidly changing environment in the Industrial Revolution 4.0 era, modern coffee shops must be able to utilize their dynamic capabilities. This study aimed to examine and explain the effect of market sensing capability and entrepreneurial orientation on strategic agility and the effects of strategic flexibility on digital transformation among modern coffee shops. The data were taken from 85 modern coffee shops in three sub-districts in Jember Regency and tested using WarpPLS 6.0. The results show that market sensing ability and entrepreneurial orientation have a significant role in influencing strategic flexibility. This research also proves that strategic flexibility influences digital transformation among modern coffee shops. Keywords: digital transformation, dynamic capability, entrepreneurial orientation, market sensing capability, strategic flexibility